One piece. Vol. 9, Tears - Oda, Eiichiro, 1975-; Amemiya, Naoko; Caselman, Lance (San Francisco : Viz Media, 2014)
When sous-chef Sanji's oceangoing restaurant is attacked by an evil pirate armada, Sanji must put aside his differences with the cooks to save the ship.
"This book reads from right to left"--Cover page [4].
"This graphic novel contains material that was originally published in English in Shonen Jump #32-35"--Page facing t.p.
Translated from the Japanese.
Adult
Adult
Keywords: Cooks -- Fiction; Pirates -- Fiction; Treasure troves -- Fiction; Buried treasure -- Fiction; Comic books, strips, etc; Cooks -- Fiction; Pirates -- Fiction; Adventure fiction; Graphic novels